Study of Correlation between Work Experience and Performance of Palm Oil Fertilization Workers in Palm Oil Plantation at PT. Citra Agro Kencana - Jamaluddin; Budi Winarni; Gregorius Rovino Batu; Muh. Yamin; Farida Aryani; Mujibu Rahman; Elisa Ginsel Popang; Edy Wibowo Kurniawan; Rahma Yanti; Mohammad Lutfi (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2025)
The continuity of operations in palm oil companies heavily relies on the quality of their human resources. This study aims to assess the relationship and impact of work experience duration on employee performance in the fertilization division. A quantitative approach was employed, using simple linear regression analysis and t-tests. The sample was selected using purposive sampling (saturation sampling), with respondents consisting of employees in the fertilization division. Data were collected through 26 questionnaires and supported by secondary information. The results indicate a positive correlation between work experience and employee performance, although the influence is not statistically significant. The low level of work experience—particularly among employees who have worked for less than a year—is the main factor behind the insignificant impact. This study also highlights the need for companies to provide training and skill development programs to enhance work experience through internal training, as well as to consider other factors such as motivation, a supportive work environment, and effective leadership.